Beyond the Spectacle of Suffering: Agnès Varda's L'Une chante, l'autre pas and Rewriting the Subject of Abortion in France - Oliver-Powell, Melissa (Feminist studies, 2020)
In the spring of 1971, three years after the revolutionary fervor of May 1968 in France, 343 women put their names to a courageous manifesto announcing that they were criminals of a particularly gendered nature. The authors of Manifeste des 343 (Manifesto of the 343) comprised a large group of culturally eminent French women and activists declaring that they had all illegally undergone abortions, which at this point, despite growing decriminalization throughout much of Western Europe, were still outlawed within their republic. Though many of the revolutionary fires had now eased to embers, French feminists demonstrated that reproductive rights were still a vital and unresolved topic of social justice. Including names as weighty as Simone de Beauvoir, Jeanne Moreau, and Catherine Deneuve, the manifesto brought together exceptional women from the fields of academia, law, theater, film and literature, alongside grassroots activists. Their action was a bold challenge to the French authorities, daring them to arrest some of the country's brightest thinkers and cultural innovators under a law the signatories felt was deeply unjust, sexist, and antithetical to the values of individual liberty and citizenship. It was a case of those with the broadest shoulders weaponizing their privilege to present a robust front line in the wider struggle for women's rights.One of the signatories was filmmaker Agnes Varda. Her name, like those of several others on the list, demonstrates the symbiosis between cultural production and gender politics that has often characterized French feminist thought. From the multidisciplinary writings of Beauvoir, to the novels of the écriture feminine movement, to the lyrical academic prose of Hélene Cixous, Luce Irigaray, Julia Kristeva, and others, French and Francophone feminist writers have tended to connect art and politics with a great deal of fluidity. As a committed activist and a filmmaker, Agnes Varda falls very much within this tradition, often adopting and developing feminist practices within her cinema. This article examines how Varda's 1977 film, L'Une chante, l'autre pas (One Sings, The Other Doesn't) interacts with and participates in the feminist political project of reproductive rights as well as the ongoing intellectual and moral debates over abortion taking place in France throughout the late 1960s and 1970s. I look particularly at the adversarial construction of abortion narratives within these debates and the location of victimhood therein. Within mainstream cultural representations in and beyond France, abortion is typically constructed as either a traumatic or a transgressive moment. The same is often true on either side of political and social debates on abortion, which have tended either to characterize the women who get abortions as irresponsible and amoral or as sympathetic victims in need of protection. Though the transgressive element persists, it is the interaction with representations of trauma that interests me here.In approaching discussions of gendered injustice, it is common for feminist writers and activists to leverage pathos as a rhetorical strategy. While suffering can be a highly effective and galvanizing expression of oppression, such discourses also run the risk of producing excessive depictions of victimhood, which can displace the capacity for action from the subject of hardship onto the privileged oppressor. This risk is particularly at stake within the cultural form of film, as its visuality and identificatory mechanics have the potential to spectacularize the female victim and make her relatable only through suffering. This was often the case in earlier French films that featured abortion such as Les Mauvaises rencontres (1955), Des gens sans importance (1956), Journal d'une femme en blanc (1965), and Une femme en blanc se revolte (1966), all of which made their subjects sympathetic by entwining them in long narratives of victimization ending in death or disgrace. This article looks at how Varda's L'Une chante, l'autre pas disengages from the spectacle of suffering that so often characterizes representations of women's experiences and rejects the idea that abortion narratives must manifest through the adversarial axis of villain and victim. Rather than producing critique only by subverting this binary and moving the woman undergoing abortion to its opposite pole - from perpetrator to victim -Varda's approach dismisses the need for such a binary altogether.Though L'Une chante has historically been overlooked within scholarship on Varda's work, it has seen a resurgence of interest in recent years and has begun to demonstrate a lively legacy among contemporary feminists. It is timely, therefore, to explore the complexities of this long-neglected work. I argue that the film takes an important, deconstructive approach toward narratives of gendered injustice, abortion in particular, that calls into question representational expectations of women's suffering. This article will proceed in four parts, with the first two giving an overview of the political climate around abortion in France, before moving on to a close analysis of Varda's film itself.